2014
DOI: 10.1002/jrs.4510
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale electromagnetic SERS enhancement on self‐assembled micropatterned gold nanoparticle films

Abstract: In this work, we demonstrate a cascaded, multiplicative electromagnetic enhancement effect in surface‐enhanced Raman scattering (SERS) on periodically micropatterned films made of colloidal gold nanoparticles, prepared by a self‐assembly approach, without implying lithography procedures. The multiplicative enhancement effect is obtained by combining surface plasmon near‐field enhancement due to nanoscale features with far‐field photonic coupling by periodic microscale features. The effect is observed for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In fact, studies on films patterned into cavity shapes and made of colloidal gold nanoparticles suggested the existence of an increased electromagnetic enhancement, presumably caused by the combination of optical interactions on two different scales: surface plasmon-enhanced near-fields due to nanoscale features and far-field photonic coupling by periodic structures at the microscale. 23 Recently, the incorporation of Au nanoparticles into the voids of SSV arrays has been explored, showing also an important increase in field enhancement at the particle-cavity junction. [24][25][26] These results reinforce the idea that electromagnetic fields in SSV arrays may be further confined by smaller metallic features at the nanometric scale.…”
Section: 18mentioning
confidence: 99%
“…In fact, studies on films patterned into cavity shapes and made of colloidal gold nanoparticles suggested the existence of an increased electromagnetic enhancement, presumably caused by the combination of optical interactions on two different scales: surface plasmon-enhanced near-fields due to nanoscale features and far-field photonic coupling by periodic structures at the microscale. 23 Recently, the incorporation of Au nanoparticles into the voids of SSV arrays has been explored, showing also an important increase in field enhancement at the particle-cavity junction. [24][25][26] These results reinforce the idea that electromagnetic fields in SSV arrays may be further confined by smaller metallic features at the nanometric scale.…”
Section: 18mentioning
confidence: 99%
“…The EF that confirms the efficiency of SERS signal has been estimated using formulae: EF = (I SERS /N ads )/(I bulk /N bulk ), where I SERS is the intensity of selected vibrational mode in the SERS experiment, I bulk is the intensity of the same Raman mode in the spectrum recorded for bulk material, N ads is the number of molecules adsorbed and probed in SERS experiment, and N bulk is the number of molecules probed in confocal volume of the optical system of Raman experiment [28][29][30]. The estimated number of R6G molecules on the area of laser spot N ads assuming close packing is equal to [28][29][30]. The obtained results proved usefulness of CD-R based substrate containing silver nanostructures for enhancement of Raman signal.…”
Section: Resultsmentioning
confidence: 99%
“…Yang and coworkers reported shape control of Ag bowls for practical SERS Substrates . Farcau and coworkers reported multiscale electromagnetic SERS enhancement on self‐assembled micropatterned gold nanoparticle films …”
Section: New Development In Colloidal Lithographymentioning
confidence: 99%